The tale of jamu : the green gold of Indonesia / Martha Tilaar, Bernard T. Widjaja; editor, Intarina Hardiman - Tilaar, Martha, ; Bernard T. Widjaja ; Intarina Hardiman (Gramedia Pustaka Utama, 2015)
162 halaman : foto berwarna, ilustrasi berwarna ; 24 cm